Effective Vocabulary Teaching Techniques for EFL Teachers in Primary Classrooms - Kusumawati, Byas Intan; Arifin, Syaadiah (English Education Department at FKIP Nommensen University, 2024)
The aim of this study is to explore vocabulary teaching techniques applied by EFL teachers in primary schools in Depok, Indonesia. Using a qualitative case study approach, the study involved observations, semi-structured interviews, and document analysis as primary data collection methods. Three EFL female teachers from three primary schools in Depok participated in this research. The findings reveal that repetition drills and translation are the most commonly used strategies due to their effectiveness in vocabulary retention and comprehension. Visual aids and interactive activities like games also play a significant role, though their use is often limited by resource constraints, and large class sizes. The research suggests that combining traditional methods with innovative approaches can improve vocabulary teaching, but further support in terms of resources and professional development is necessary for teachers to maximize their effectiveness. The study recommends future research focusing on digital tools and technology-based interventions, assessing the impact of teacher training programs, and comparing urban and rural contexts. Additionally, exploring the long-term effects of these techniques on students’ language proficiency would provide valuable insights for enhancing English education in Indonesia.